Judging evil : rethinking the law of murder and manslaughter - Pillsbury, Samuel H. (New York University Press, 1998)
Why do killers deserve punishment? How should the law decide? These are the questions Samuel H. Pillsbury seeks to answer in this important new book on the theory and practice of criminal responsibility. In an argument both traditional and fresh, Pillsbury holds that persons deserve punishment according to the evil they choose to do, regardless of their psychological capacities. Using real case examples, he offers concrete proposals for legal reform, urging that modern preoccupations with subjective aspects of wrongdoing be replaced with rules that focus more on the individual's motives.